Molecular study of digenean diversity in aquatic organisms in northern Norway, with a focus on the seasonality of Crepidostomum [Braun, 1900] - Slåteng, Sigurd (UiT Norges arktiske universitet, 2022)
This study aimed to elucidate cryptic trematode diversity across multiple life stages in aquatic organisms. I collected samples from first intermediate hosts (bivalves), second intermediate hosts (amphipods and insect nymphs), and definitive hosts (fish), and identified them by use of molecular methods. Phylograms based on molecular markers from 28S and COI genes were used to identify nine species from three families of trematodes. One of the species, Bunodera vytautasi, is new to Europe, and three of the species were found in putative new intermediate hosts. Phylograms were also made for the bivalve hosts of these trematodes, which permitted the identification of sphaeriid clams. My findings give further insights on the diversity of trematodes and their distributions in northern aquatic systems, as well as information on the macroinvertebrate hosts of trematodes. Further, I observed some preliminary patterns on the seasonality of Crepidostomum in Arctic char and brown trout by looking at the species distribution from two sampling seasons. I observed a pattern where C. farionis and C. metoecus seem to infect and mature in fish at different seasons. Juvenile C. farionis stages were more common in the summer samples, and adults in the late autumn sample. C. metoecus were proportionally scarce compared to C. farionis, apart from the Arctic char autumn sample, where multiple juveniles were found. This pattern is likely to be attributed to fish predation on the second intermediate host where C. farionis infects insect larva, a prey item commonly consumed during the summer. C. metoecus on the other hand is the only species of Crepidostomum found to parasitise the amphipod Gammarus lacustris, a prey item Arctic char consumes more of during late autumn and winter. These findings give preliminary information on the seasonal variation closely related trematode species can have regarding their timing of trophic transmissions.